Magic tree house Olympic challenge! - Osborne, Mary Pope; Masson, Philippe (Red Fox London, 2010)
'It's off to Ancient Greece for the children and the tree house! They land just in time for the exciting Olympic Games, with the athletes, wrestlers and chariot racers all ready to go. But when Annie finds out no girls are allowed, there's trouble in store...'--Back cover